2010
DOI: 10.1111/j.1365-3032.2009.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the phonotactic selectiveness of four species of chirping crickets (Gryllidae): Implications for call recognition

Abstract: Earlier studies of phonotaxis by female crickets describe this selective behavioural response as being important in the females' choices of conspecific males, leading to reproduction. In the present study, moderate (30+) to very large data sets of phonotactic behaviour by female Acheta domesticus L., Gryllus bimaculatus DeGeer, Gryllus pennsylvanicus Burmeister and Gryllus veletis Alexander demonstrate substantially greater plasticity in the behavioural choices, as made by females of each species, for the syll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(65 citation statements)
references
References 27 publications
(77 reference statements)
5
60
0
Order By: Relevance
“…Male G. pennsylvanicus signaled more often (14 versus 9 min/hr), louder (62 vs 60 dB), with elevated carrier frequencies (4.7 vs 4.6 kHz), shorter interpulse durations (38 vs 40 msec), and shorter pulse periods (57 vs 59 msec) during the high versus low mating activity time periods, respectively (high 22∶00–09∶59 vs low 10∶00–21∶59; [32]). This plasticity appears adaptive given that female G. pennsylvanicus preferentially mate with males that signal most often [63] and are more attracted to loud signals played at 5 kHz versus quiet ones played at 4 kHz, and signals with pulse periods falling within the 35–60 msec range [49], [54]. Male G. veletis signaled more often (7 vs 3 min/hr), with longer interpulse durations (37 vs 35 msec), longer pulse periods (53 vs 50 msec) and longer chirp durations (128 vs 118 msec) during the high versus low mating activity time periods (high 04∶00–15∶59 vs low 16∶00–03∶59; [32]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male G. pennsylvanicus signaled more often (14 versus 9 min/hr), louder (62 vs 60 dB), with elevated carrier frequencies (4.7 vs 4.6 kHz), shorter interpulse durations (38 vs 40 msec), and shorter pulse periods (57 vs 59 msec) during the high versus low mating activity time periods, respectively (high 22∶00–09∶59 vs low 10∶00–21∶59; [32]). This plasticity appears adaptive given that female G. pennsylvanicus preferentially mate with males that signal most often [63] and are more attracted to loud signals played at 5 kHz versus quiet ones played at 4 kHz, and signals with pulse periods falling within the 35–60 msec range [49], [54]. Male G. veletis signaled more often (7 vs 3 min/hr), with longer interpulse durations (37 vs 35 msec), longer pulse periods (53 vs 50 msec) and longer chirp durations (128 vs 118 msec) during the high versus low mating activity time periods (high 04∶00–15∶59 vs low 16∶00–03∶59; [32]).…”
Section: Discussionmentioning
confidence: 99%
“…Note, signaling time represents the total amount of time the individual spent signaling in that hour, whereas the other eight signaling parameters are represented by mean parameter values for that hour. We included pulse period, even though it is not a separate trait but instead combines pulse duration and interpulse duration, because females are known to prefer species specific pulse periods ( G. pennsylvanicus : 35–60 msec [49], [54], G. veletis : 40–70 msec [54]). We included pulse duration and interpulse duration so that we could know what component of the signal males were changing to change pulse period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional reason for our contrasting results may be that mating history, rather than female age, has a predominant effect on choosiness in G. lineaticeps. Although females differed in age, which has been shown to affect mate choosiness in other species (Gray, 1999;Stout et al, 2010), they did not differ in mating history, which has also been shown to affect mate choosiness (Lickman et al, 1998). In a previous study, we found a significant effect of the interaction between female age and perceived male density: young females adjusted their choosiness based upon male density, whereas older females did not (Atwell and Wagner, 2014).…”
Section: Discussionmentioning
confidence: 45%
“…Selection should thus favor individuals who can accurately asses and adjust their choosiness to the current risk of predation (Lima and Dill, 1990;Kavaliers and Choleris, 2001). Female mate choosiness has also been shown to decrease with age (Gray, 1999;Stout et al, 2010) due to a decreased ability to invest in searching for preferred males (Cotter et al, 2011). Older females may also show less predation-related plasticity in choosiness.…”
Section: Introductionmentioning
confidence: 96%